THE MODEL OF FORMATION OF PROFESSIONAL AND CREATIVE POTENTIAL OF STUDENTS OF CREATIVE PROFESSIONS - Elena A. Gnatyshina; Natalia A. Gerdt (Russian State Vocational Pedagogical University, 2015)
The aim of publication is to acquaint readers with the practical aspects of simulation of the process of formation of professional and creative potential of students in terms of professional educational organizations, on the basis of which the authors suggest a model that provides better students' preparation for the profession of engineering and the art of photography. Methods. The authors use scientific-pedagogical analysis of the concepts forming the conceptual field problems, theoretical and methodological analysis of the problem of modeling on the basis of which we have developed and described a model of formation of professional and creative potential of students. The systematic, personal activity and competence-oriented approaches are selected as a conceptual basis for developing models of formation of professional and creative potential of students. The model is based on the principles of humanity, scientific, consistency, adequacy, effectiveness, the theory with the practice combination, focus on the potential of subjects of the educational environment and technology. Results. The model of formation of professional and creative potential of students of creative professions is described and graphically presented. This model allows improving the quality of training of the future workforce, which is one of the most urgent tasks of the state policy of Russia. Scientific novelty. The proposed model presents the peculiarities of training of students of vocational educational institutions. Functions and indicative data of realisation of each component of the given model are considered. The model represents the integration of the following components: motivational and target, substantive, procedural, reflective and evaluative. Practical significance. The proposed model complies with modern society on the quality of training of students of creative professions in terms of professional educational organizations; it reflects the interdisciplinary communication disciplines, making it available for use not only by teachers of special and technical disciplines, but also teachers of general subjects. Model use in teaching and educational process will allow raising its quality.